2022
DOI: 10.1111/cpr.13361
|View full text |Cite
|
Sign up to set email alerts
|

Lack of SIRP‐alpha reduces lung cancer growth in mice by promoting anti‐tumour ability of macrophages and neutrophils

Abstract: Objectives: Signal regulatory protein-alpha (SIRPα) is a transmembrane glycoprotein specifically expressed on myeloid cells. Blockade of SIRPα/CD47 interaction is effective in combinational therapy of some cancers. This study aimed to explore into the role and underlying molecular mechanisms of SIRPα in lung cancer growth. Materials and Methods: A mouse model with lung cancer in wild-type (WT) and SIRPα-knockout mouse (KO) mice was established by subcutaneous injection of Lewis murine lung cancer cells (LLC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…38 On CD47-SIRPα blockade, it elicits a prophagocytic signal to potentiate tumor control via increasing tumor cell phagocytosis, which has emerged as a novel immune checkpoint inhibitor in various cancer patients. 39 Moreover, the decreased SIRPα level has been discovered in some patients diagnosed with malignancies. 40 According to our experiment, it is worth noting that the declined SIRPα signal might induce excessive synaptic clearance in microglia towards GABAergic synapse in the central nervous system in the murine bone cancer pain model, which is in conjunction with their pain-related behavior.…”
Section: Discussionmentioning
confidence: 99%
“…38 On CD47-SIRPα blockade, it elicits a prophagocytic signal to potentiate tumor control via increasing tumor cell phagocytosis, which has emerged as a novel immune checkpoint inhibitor in various cancer patients. 39 Moreover, the decreased SIRPα level has been discovered in some patients diagnosed with malignancies. 40 According to our experiment, it is worth noting that the declined SIRPα signal might induce excessive synaptic clearance in microglia towards GABAergic synapse in the central nervous system in the murine bone cancer pain model, which is in conjunction with their pain-related behavior.…”
Section: Discussionmentioning
confidence: 99%
“…28 Previous study pointed that suppressing lung cancer cell growth in mice is dependent on circulating macrophages and neutrophils. 29 Macrophages are one of the primary cell types that drive the production of MCP-1 and LTB4. 26,30 A previous study showed a parallel increase of Galectin-3 level and the number of MDSCs in mice after cisplatin treatment, 31 which provokes our interest.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many chemokines or cytokines, MCP‐1 is a vital monocyte‐attracting chemokine with strong chemotaxis activity, and potently recruits blood monocytes to inflammatory or tumour sites 26,27 ; LTB4 is a chemokine with a strong effect on neutrophils, playing an important role in the chemotaxis and infiltration of neutrophils 28 . Previous study pointed that suppressing lung cancer cell growth in mice is dependent on circulating macrophages and neutrophils 29 . Macrophages are one of the primary cell types that drive the production of MCP‐1 and LTB4 26,30 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of this interaction leads to an increasing phagocytosis of tumor cells by macrophages [12] , [16] , [18] . SIRP- α deficiency also enhances phagocytotic activity of neutrophils during lung cancer [19] . In the context of repAMI it was also shown that inhibition of CD47 enhances phagocytosis of cardiac cell debris by macrophages leading to a reduced infarction area [20] .…”
Section: Introductionmentioning
confidence: 99%